Punção em lajes cogumelo : estudo da retangularidade dos pilares - MOURO, Valéria Conceição (2006)
Eight reinforced concrete square flat slabs of reinforced concrete were tested. Slabs were 130mm thick with an 1800 mm side and were submitted to central loading, and the objective was to investigate the influence of column rectangularity coefficient. Column cross section dimensions (cmáx/cmín) varyied between 1 and 4, with a constant perimeter equal to 1000mm. Results presented and analysed include ultimate loads and failure types, modes of rupture, vertical displacements, cracking and deformations of steel and concrete. Comparisons with codes, norms and results of literature results are also presented. The results indicate that as the rectangularity coefficient increases, punching shear resistance decreases for constant perimeter column flat slabs. Suggesting that punching shear has to be considered specially in regions close to column extremity, where there is a larger concentration of shear forces. A proposal for an inclusion of the retangularity parameter (cmáx/cmín) in expressions for calculation punching shear resistance of ACI (2002), CEB-FIP (1991), EC2 (2001) and NBR-6118 (2003) codes is presented.